1982
DOI: 10.1002/app.1982.070270408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reactant ratio and temperature on the characteristics of phenol–formaldehyde foams

Abstract: SynopsisThis study presents experimental results on the preparation and characteristics of high-density phenol-formaldehyde foams and compares their characteristics with the available patent literature. An extrapolation of the data has been used to identify the relevant process parameters used for the preparation of lower-density foams. The effect of catalyst combination and phenol formaldehyde molar ratio on the ease of foaming and its ultimate strength has been investigated. A total solidsrefractive index co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Li et al reported that different molar ratios of phenol to paraformaldehyde significantly influenced the properties and molecular structure of the synthesized resin. Singh and Ohri reported that both reaction temperature and speed were closely related to the activity of PF resin.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported that different molar ratios of phenol to paraformaldehyde significantly influenced the properties and molecular structure of the synthesized resin. Singh and Ohri reported that both reaction temperature and speed were closely related to the activity of PF resin.…”
Section: Introductionmentioning
confidence: 99%
“…With deficiencies such as the mechanical strength, high open cell content, and corrosion having been resolved to a great extent (except for friability), this study was undertaken to reduce the overly high contents of free phenol and free formaldehyde in phenolic foam. A trend of decreasing free phenol and free formaldehyde during the synthesis of resols has been reported in recent years 1–4. Manfredi et al5 gave the results of free phenol and free formaldehyde contents with different formaldehyde/phenol (F/P) molar ratios.…”
Section: Introductionmentioning
confidence: 91%
“…A trend of decreasing free phenol and free formaldehyde during the synthesis of resols has been reported in recent years. [1][2][3][4] Manfredi et al 5 gave the results of free phenol and free formaldehyde contents with different formaldehyde/phenol (F/P) molar ratios. We investigated the literature and found that there was little information on reducing the contents of free phenol and free formaldehyde in phenolic foam.…”
Section: Introductionmentioning
confidence: 99%
“…Fire and environmental pollution problems caused by inflammable foams have aroused worldwide public concern [1,2]. In the past few decades, considerable research efforts have been devoted to the formulation and characterization of new ecologically friendly flame-retardant foams that can be applied in indoor decoration and wall heat-preservation fields [3].…”
Section: Introductionmentioning
confidence: 99%